DEVELOPMENT OF ANDROID-BASED INTERACTIVE LEARNING MEDIA USING ISPRING SUITE 11 AND QR CODES ON THE HUMAN IMMUNE SYSTEM MATERIAL FOR GRADE XI HIGH SCHOOL STUDENTS - Nabila Haq; Zulfarina; Darmadi (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The advancement of technology in education demands innovations in learning media that can enhance students’ motivation, interaction, and understanding. In the topic of the Human Immune System, students often struggle to grasp abstract concepts such as immune mechanisms, antigen–antibody interactions, and physiological responses, while learning facilities at school remain limited and lecture-based methods still dominate the learning process. iSpring Suite 11 offers a solution because it enables the development of interactive learning media that can be easily accessed via Android devices, equipped with materials, videos, animations, and quizzes, and can be flexibly distributed through QR Codes. This study aims to produce high-quality Android-based interactive learning media using iSpring Suite 11 and QR Codes for Grade XI students on the Human Immune System topic. The research employed the ADDIE development model with assessment instruments in the form of validation questionnaires and student response questionnaires using a Likert scale. Evaluations were conducted by material experts, media experts, and students during a limited trial stage. The results showed that the developed interactive learning media obtained an average quality score of 3.68, categorized as very good, covering aspects of content feasibility, appearance, interactivity, ease of use, and usefulness in supporting learning. Therefore, the Android-based media using iSpring Suite 11 and QR Codes is classified as having very good quality and is suitable for use in the learning process.